Mesoscale modulation of air‐sea CO2 flux in Drake Passage. Issue 9 (10th September 2016) - Song, Hajoon; Marshall, John; Munro, David R.; Dutkiewicz, Stephanie; Sweeney, Colm; McGillicuddy, D. J.; Hausmann, Ute
Abstract: We investigate the role of mesoscale eddies in modulating air‐sea CO2 flux and associated biogeochemical fields in Drake Passage using in situ observations and an eddy‐resolving numerical model. Both observations and model show a negative correlation between temperature and partial pressure of CO2 ( p CO2 ) anomalies at the sea surface in austral summer, indicating that warm/cold anticyclonic/cyclonic eddies take up more/less CO2 . In austral winter, in contrast, relationships are reversed: warm/cold anticyclonic/cyclonic eddies are characterized by a positive/negative p CO2 anomaly and more/less CO2 outgassing. It is argued that DIC‐driven effects on p CO2 are greater than temperature effects in austral summer, leading to a negative correlation. In austral winter, however, the reverse is true. An eddy‐centric analysis of the model solution reveals that nitrate and iron respond differently to the same vertical mixing: vertical mixing has a greater impact on iron because its normalized vertical gradient at the base of the surface mixed layer is an order of magnitude greater than that of nitrate. Key Points: Both observations and models reveal mesoscale modulation of CO2 flux near Drake Passage CO2 flux varies seasonally due to the changes in the balance between solubility and biogeochemical effects Anomalous vertical mixing is the key physical process that drives CO2 flux modulation